2014
DOI: 10.1175/jas-d-12-0343.1
|View full text |Cite
|
Sign up to set email alerts
|

Can the Delay in Antarctic Polar Vortex Breakup Explain Recent Trends in Surface Westerlies?

Abstract: The authors test the hypothesis that recent observed trends in surface westerlies in the Southern Hemisphere are directly consequent on observed trends in the timing of stratospheric final warming events. The analysis begins by verifying that final warming events have an impact on tropospheric circulation in a simplified GCM driven by specified equilibrium temperature distributions. Seasonal variations are imposed in the stratosphere only. The model produces qualitatively realistic final warming events whose i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…FWs are also observed to have a similar tropospheric impact, although its latitudinal structure differs somewhat from the annular-mode form (Black et al 2006;Black and McDaniel 2007a,b;Hu et al 2014b), and uppertropospheric planetary-scale waves may play a role (Sun et al 2011). Similar results have been found in simplified global models (Sun and Robinson 2009;Sun et al 2011;Sheshadri et al 2014).…”
Section: Introductionsupporting
confidence: 57%
“…FWs are also observed to have a similar tropospheric impact, although its latitudinal structure differs somewhat from the annular-mode form (Black et al 2006;Black and McDaniel 2007a,b;Hu et al 2014b), and uppertropospheric planetary-scale waves may play a role (Sun et al 2011). Similar results have been found in simplified global models (Sun and Robinson 2009;Sun et al 2011;Sheshadri et al 2014).…”
Section: Introductionsupporting
confidence: 57%
“…Due to the relatively quiescent nature of the SH stratospheric winter, the timing of the final warming is not as variable in the SH compared to the NH (Black et al, ; Waugh & Rong, ). However, a trend toward a later breakup of the polar vortex due to the stratospheric cooling trend has been observed (Waugh et al, ), with potentially important implications for the SH troposphere (Byrne et al, ; Sheshadri et al, ; L. Sun et al, ).…”
Section: A Brief Overview Of the Stratospheric Circulationmentioning
confidence: 99%
“…In the Southern Hemisphere, the polar vortex also exhibits a strong long-term trend: a strengthening trend can be observed for the season from November to March (Thompson and Solomon 2002), accompanied by a trend in the timing of the final warming toward a later breakup of the polar vortex (Waugh et al 1999;Black and McDaniel 2007;Sheshadri et al 2014), which is suggested to be caused by ozone depletion in spring (Ramaswamy et al 2001;Thompson et al 2011). Ozone depletion was observed to be especially strong between 1979 and about 2000 (Solomon 1999), with a recovery starting after that (Oman et al 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Here, JFM is used for the definition of the summer season to avoid including the large variability due to mixing following Rossby wave breaking, which is associated with the final warming, which, for example, in NCEP reanalysis for 1960-2010 occurs between late October and early December (e.g., Sheshadri et al 2014). Here, JFM is used for the definition of the summer season to avoid including the large variability due to mixing following Rossby wave breaking, which is associated with the final warming, which, for example, in NCEP reanalysis for 1960-2010 occurs between late October and early December (e.g., Sheshadri et al 2014).…”
Section: Probability Density Functionsmentioning
confidence: 99%